Invisible Labour, Transnational Lives: Gendered Work and New Social Fields in Coastal Philippines - Barber, Pauline Gardiner (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1995)
Feminist research on gender relations in fishing communities has established that through a narrowing of focus upon maritime pursuits, the coast is masculinized and men’s lives are privileged over women’s. The invisibility of women’s labour in coastal communities becomes particularly acute in situations where the labour is performed somewhere else, as is the case here. This comparison of gendered work practices and ideologies in some Philippines coastal households reveals that women’s work is crucial to the reproduction of fisheries sectors. But more than this, most coastal households are not sustained primarily through the fishery, nor through the labour of a male breadwinner. Nonetheless, local gender ideologies overstate men’s contributions to livelihood and understate the economic and social significance of women’s work: productive and reproductive; local and extra-local. Increasingly, the exporting of women’s labour "in service" is both a means of household livelihood and ironically, a strategy for servicing the national debt. Gendered class and cultural affinities are now articulated through transnational social fields creating new forms of consciousness and possibilities for political expression.